Interactions Between Pathogenic Burkholderia and the Complement System: A Review of Potential Immune Evasion Mechanisms - Syed, Irum; Wooten, R. Mark (Frontiers in Cellular and Infection Microbiology, 2021)
The genus Burkholderia contains over 80 different Gram-negative species including both plant and human pathogens, the latter of which can be classified into one of two groups: the Burkholderia pseudomallei complex (Bpc) or the Burkholderia cepacia complex (Bcc). Bpc pathogens Burkholderia pseudomallei and Burkholderia mallei are highly virulent, and both have considerable potential for use as Tier 1 bioterrorism agents; thus there is great interest in the development of novel vaccines and therapeutics for the prevention and treatment of these infections. While Bcc pathogens Burkholderia cenocepacia, Burkholderia multivorans, and Burkholderia cepacia are not considered bioterror threats, the incredible impact these infections have on the cystic fibrosis community inspires a similar demand for vaccines and therapeutics for the prevention and treatment of these infections as well. Understanding how these pathogens interact with and evade the host immune system will help uncover novel therapeutic targets within these organisms. Given the important role of the complement system in the clearance of bacterial pathogens, this arm of the immune response must be efficiently evaded for successful infection to occur. In this review, we will introduce the Burkholderia species to be discussed, followed by a summary of the complement system and known mechanisms by which pathogens interact with this critical system to evade clearance within the host. We will conclude with a review of literature relating to the interactions between the herein discussed Burkholderia species and the host complement system, with the goal of highlighting areas in this field that warrant further investigation.